Premise plumbing bacterial communities in four European cities and their association with Legionella - Scaturro, Maria; Del Chierico, Federica; Motro, Yair; Chaldoupi, Angeliki; Flountzi, Anastasia; Moran-Gilad, Jacob; Girolamo, Antonietta; Koutsiomani, Thomai; Krogulska, Bozena; Lindsay, Diane; Matuszewska, Renata; Papageorgiou, Georgios; et al. (Frontiers in Microbiomes, 2023)
Legionella species are Gram negative, facultative, intracellular bacteria found in natural and engineered water systems. Understanding the bacterial interactions underlying the success of Legionella in aquatic environments could be beneficial for control. We aimed to profile, by 16S rRNA amplicon sequencing, the bacterial communities in premise plumbing systems of buildings in four European cities (Copenhagen, Warsaw, Rome, Athens), and identify positive and negative associations of specific community members to culturable Legionella. The coarse taxonomic composition was similar across the four cities, but Copenhagen and Warsaw had richer, more diverse communities than Athens and Rome, with a greater number of city-specific amplicon sequence variants (ASVs). The cities had statistically significant differences in bacterial communities at the ASV level, with relatively few shared ASVs. Out of 5,128 ASVs, 73 were classified as Legionella, and one or more of these were detected in most samples from each city (88.1% overall). Interestingly, the relative abundance of Legionella ASVs did not correlate with Legionella culture status. Overall, 44.2% of samples were Legionella culture positive: 71.4% in Warsaw, 62.2% in Athens, 22.2% in Rome, and 15.2% in Copenhagen. 54 specific ASVs and 42 genera had significant positive or negative associations with culturable Legionella. Negative associations included Staphylococcus, Pseudomonas, and Acinetobacter. Positive associations included several Nitrospira ASVs and one classified as Nitrosomodaceae oc32, ASVs in the amoeba-associated genera Craurococcus-Caldovatus and Reyranella, and the predatory genus Bdellovibrio. Some of these associations are well supported by laboratory studies, but others are the opposite of what was expected. This highlights the difficulties in translating pure culture results to into complex real-life scenarios. However, these positive and negative associations held across the four cities, across multiple buildings and plumbing compartments. This is important because developing better control measures, including probiotic approaches, will require an understanding of ecological relationships that can be generalised across different engineered water systems.